2015
DOI: 10.56093/ijas.v85i11.53700
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrition, harvesting date and fruit canopy position on yield and quality of Kinnow mandarin (Citrus nobilis x Citrus deliciosa)

Abstract: Attractive peel colour and quality development in Kinnow (Citrus nobilis Lour x Citrus deliciosa Tenara) is a prime requisite for its fair market price. The objective of study was to find out the impact of canopy position, date of harvesting and nutrition on yield and quality of Kinnow mandarin. A field experiment was conducted in a four year old Kinnow orchard using factorial randomized block design with three replications. There were nine treatments comprised of various N, P, K levels and one control; two ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…Regarding canopy position, this study showed that outside (sun-exposed) fruit had higher TSS but lower juice content and colour lightness than inside (shadowed) fruit. This is in agreement with the results reported by Thakre et al (2015) and Olarewaju et al (2018), who found that fruit from the external canopy had higher TSS and total carotenoids than fruit from the internal canopy. From all the positions studied, fruit on the lower inside canopy showed the highest juice content and ascorbic acid, and the lowest TSS, TA, and fructose and glucose content, while the upper outside fruit had the opposite results.…”
Section: The Effect Of Harvest Time and Canopy Position On The Postha...supporting
confidence: 93%
See 3 more Smart Citations
“…Regarding canopy position, this study showed that outside (sun-exposed) fruit had higher TSS but lower juice content and colour lightness than inside (shadowed) fruit. This is in agreement with the results reported by Thakre et al (2015) and Olarewaju et al (2018), who found that fruit from the external canopy had higher TSS and total carotenoids than fruit from the internal canopy. From all the positions studied, fruit on the lower inside canopy showed the highest juice content and ascorbic acid, and the lowest TSS, TA, and fructose and glucose content, while the upper outside fruit had the opposite results.…”
Section: The Effect Of Harvest Time and Canopy Position On The Postha...supporting
confidence: 93%
“…However, the results showed that the rind of fruit harvested in March was redder and there was less variability in colour hue within canopy positions. This confirms previous studies where 'Kinnow' mandarins harvested in India during the last week of December had higher ascorbic acid and total carotenoid content in the peel and juice than fruit harvested two weeks later (Thakre et al, 2015). Similarly, early maturing cultivars of satsumas ('Iwasaki', 'Okitsu', and 'Goku Wase') had higher absorption of carotenoids in the juice vesicles and advanced colour changes in the flavedo than latematuring (Sun et al, 2021).…”
Section: The Effect Of Harvest Time and Canopy Position On The Postha...supporting
confidence: 88%
See 2 more Smart Citations